Optimizing Evaporator Design in ORC Systems for Waste-to-Energy Conversion Using FAST Diagram and Value Engineering - Wibowo, R. Susalit Setya; Satmintareja, Satmintareja; Abdurahman, Asep Duduh; Suyatmin, Suyatmin; Darmawan, Darmawan; Gunawan, Ari; Budiarti, Kusumawati Dewi; Baddu, Nasrul; Pramono, Adhi; Faisal, Faisal; Nugroho, Cahyono; Ngudiwaluyo, Suharto; Putra, Zico Pratama (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
The global waste crisis necessitates innovative solutions for sustainable energy conversion. This study presents a comprehensive optimization framework for evaporator design in Organic Rankine Cycle (ORC) systems utilized in waste-to-energy conversion. This research integrates the Function Analysis System Technique (FAST) diagram with Value Engineering (VE) principles to assess the logical hierarchy and cost analysis components of system effectiveness. Evaluation of the 887 kW shell-and-tube evaporator showed tubes, baffles, and shells account for 90% of production costs and are the most thermally efficient components. Further strategic redesign under VE principles resulted in 23% cost reduction with 15% efficiency improvements, demonstrating resource expenditure without performance compromise. The proposed approach offers a foundational methodology for advancing enduring ORC system design while harnessing high waste-to-value electrical energy conversion at low expenses, fostering the circular economy.